LeverAge: A European network to leverage the multi-age workforce - Marcus, J.; Scheibe, S.; Kooij, D.; Truxillo, D. M.; Zaniboni, S.; Abuladze, L.; Al Mursi, N.; Bamberger, P. A.; Balytska, M.; Betanzos, N. D.; Perek-Białas, J.; Boehm, S. A.; et al. (Work, Aging and Retirement, 2024)
Bringing together 150+ scholars and practitioners from 50+ countries, and funded by the European Commission, COST Action LeverAge (https://www.cost.eu/actions/CA22120/) is the first network-building project of its kind in the work and organizational psychology and human resource management (WOP/HRM) aspects of work and aging. Focused on the aging workforce, the Action aims to foster interdisciplinary and multinational scientific excellence and the translation of science to practical and societal impact across 4 years. Based on a research synthesis, we identify five broad research directions for work and aging science including work and organizational practices for a multi-age workforce, successful aging at work, the integration of age-diverse workers and knowledge transfer, aging and technology at work, and career development in later life and retirement. We provide key research questions to guide scientific inquiry along these five research directions alongside best practice recommendations to expand scholarly impact in WOP/HRM.